2015
DOI: 10.1371/journal.pone.0141826
|View full text |Cite
|
Sign up to set email alerts
|

FL3, a Synthetic Flavagline and Ligand of Prohibitins, Protects Cardiomyocytes via STAT3 from Doxorubicin Toxicity

Abstract: AimsThe clinical use of doxorubicin for the treatment of cancer is limited by its cardiotoxicity. Flavaglines are natural products that have both potent anticancer and cardioprotective properties. A synthetic analog of flavaglines, FL3, efficiently protects mice from the cardiotoxicity of doxorubicin. The mechanism underlying this cardioprotective effect has yet to be elucidated.Methods and ResultsHere, we show that FL3 binds to the scaffold proteins prohibitins (PHBs) and thus promotes their translocation to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 38 publications
3
25
0
Order By: Relevance
“…A recent study showed that FL3 treatment could influence the localization of PHB in cardiomyocytes by promoting PHB translocation from nucleus to mitochondria [ 13 ], however, it remains to be determined in UCB cells. We first measured the total PHB protein levels of FL3-treated T24 cells, and the result showed that the protein levels of PHB was slowly decreased by FL3 treatment (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study showed that FL3 treatment could influence the localization of PHB in cardiomyocytes by promoting PHB translocation from nucleus to mitochondria [ 13 ], however, it remains to be determined in UCB cells. We first measured the total PHB protein levels of FL3-treated T24 cells, and the result showed that the protein levels of PHB was slowly decreased by FL3 treatment (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have shown that flavaglines can directly binds to PHB to inhibit the activation of PHB-mediated signaling pathways, consequently leading to inhibition of protein synthesis, cell cycle progression, and cell growth in cancer cells [ 12 , 31 , 32 ]. Meanwhile, flavaglines present little cytotoxicity to healthy cells at nanamolar concentrations [ 13 , 16 , 33 , 34 ]. Therefore, the discovery of flavaglines brings new hope for the treatment of UCB.…”
Section: Discussionmentioning
confidence: 99%
“…This is especially important because most STAT3 inhibitors designed to date target STAT3’s SH2 domain, which likely would not affect mitoSTAT3’s activity because the SH2 domain is dispensable for its mitochondrial function (1, 2). Certain pharmacological treatments affect mitoSTAT3 abundance, although their widespread use in manipulating the mitoSTAT3 pathway remains to be determined (48, 49). For instance, phospho–valproic acid limits the translocation of mitoSTAT3 in a pancreatic cancer cell model, which leads to increased cancer cell death (48), pointing to the value in targeting mitoSTAT3.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, drug combination is one of the main strategies for ADM use. Cumulative data have demonstrated that ADM-induced cardiotoxicity is reduced by some natural products, such as Tanshinone IIA, 19 flavaglins, 20 and resveratrol, 21 through various types of mechanisms in cells and animal models. THSG is a resveratrol analog with an additional glycoside moiety that increases the hydrophilicity of aglycone and promotes excretion in the urine.…”
Section: Discussionmentioning
confidence: 99%